(untitled) (Modern American Journal of Biological and Environmental Sciences, 2026)
This article reviews the theoretical foundations of the pedagogical observation method, its main types and practical application in medical education. The observation method is analyzed as one of the main tools for assessing clinical skills, monitoring student development and improving the quality of education in the process of training medical specialists. Various forms of observation - systematic, free, participatory and direct observation types and their variants adapted to medical education are presented. The results of the study show that the correct use of the observation method allows for an objective assessment of the student’s professional competence in clinical practice.